Effect of Scratch on 5th Graders’ Algorithm Development and Computational Thinking Skills - Ali Oluk, Özgen Korkmaz, Hayriye Ayşe Oluk (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
This study aimed to investigate the effect of using Scratch on developing skills related to algorithm development and computational thinking. The quasi experimental study with a pretest-posttest control group design was carried out with 62 (31assigned to Experimental and assigned to Control group respectively) 5th grader students. The study was conducted in a 6-week period during information technologies and software classes. The experimental group students were taught algorithms by using the Scratch program while control group students learned algorithms with the help of the current curriculum. Students were administered Computational Thinking Scale and Algorithm Development Achievement Test as pre and post-tests. The required factor and reliability analyses were carried out for computational thinking scale and Cronbach’s Alpha reliability coefficient was calculated as 0.809. KR-20 internal consistency coefficient for Algorithm Development Achievement Test was found to be 0.85. Independent Samples t test was administered to see whether there was a statistically significant difference between the groups’ achievement test results. Results show that experimental group students’ skills regarding algorithm development and computational thinking significantly developed compared to those of the control group. Based on the findings, it can be argued that Scratch Program is a learning tool that can be used to develop skills related to algorithm development and computational thinking.